Creatine as nutritional supplementation and medicinal product - Benzi, G.; Ceci, A. (The Journal of Sports Medicine and Physical Fitness, 2001)
Because of assumed ergogenic effects, the creatine administration has become popular practice among subjects participating in different sports. Appropriate creatine monohydrate dosage may be considered a medicinal product since, in accordance with the Council Directive 65/65/EEC, any substance which may be administered with a view to restoring, correcting or modifying physiological functions in humans beings is considered a medicinal product. Thus, quality, efficacy and safety must characterise the substance. In addition, the European Court of Justice has held that a product which is recommended or described as having preventive or curative properties is a medicinal product even if it is generally considered as a foodstuff and even if it has no known therapeutic effect in the present state of scientific knowledge. In biochemical terms, creatine administration increases creatine and phosphocreatine muscle concentration, allowing for an accelerated rate of ATP synthesis. In thermodynamics terms, creatine stimulates the creatine-creatine kinase-phosphocreatine circuit, which is related to the mitochondrial function as a highly organised system for the control of the subcellular adenylate pool. In pharmacokinetics terms, creatine entry into skeletal muscle is initially dependent on the extracellular concentration, but the creatine transport is subsequently downregulated. In pharmacodynamics terms, the creatine enhances the possibility to maintain power output during brief periods of high-intensity exercises. In spite of uncontrolled daily dosage and long-term administration, no researches on creatine monohydrate safety in humans were set up by standardised protocols of clinical pharmacology and toxicology, as currently occurs in phases I and II for products for human use. More or less documented side effects induced by creatine monohydrate are weight gain; influence on insulin production; feedback inhibition of endogenous creatine synthesis; long-term damages on renal function. A major point that related to the quality of creatine monohydrate products is the amount of creatine ingested in relation to the amount of contaminants present. During the industrial production of creatine monohydrate from sarcosine and cyanamide, variable amounts of contaminants (dicyandiamide, dihydrotriazines, creatinine, ions) are generated and, thus, their tolerable concentrations (ppm) must be defined and made consumers known. Furthermore, because sarcosine could originate from bovine tissues, the risk of contamination with prion of bovine spongiform encephalopathy (BSE or mad-cow disease) can t be excluded. Thus, French authorities forbade the sale of products containing creatine. Creatine, as other nutritional factors, can be used either at supplementary or therapeutic levels as a function of the dose. Supplementary doses of nutritional factors usually are of the order of the daily turnover, while therapeutic ones are three or more times higher. In a subject of 70 kg with a total creatine pool of 120 g, the daily turnover is approximately of 2 g. Thus, in healthy subjects nourished with fat-rich, carbohydrate, protein-poor diet and participating in a daily recreational sport, the oral creatine monohydrate supplementation should be of the order of the daily turnover, i.e., less than 2.5-3 g per day, bringing the gastrointestinal absorption to account. In healthy athletes submitted daily to high-intensity strength or sprint training, the maximal oral creatine monohydrate supplementation should be of the order of two times the daily turnover, i.e., less than 5-6 g per day for less than two weeks, and the creatine monohydrate supplementation should be taken under appropriate medical supervision. The oral administration of more that 6 g per day of creatine monohydrate should be considered as a therapeutic intervention and should be prescribed by physicians only in the cases of suspected or proven deficiency, or in conditions of severe stress and/or injury. The incorporation of creatine into the medicinal product class is supported also by the use in pathological conditions, e.g., some mitochondrial cytopathies, the guanidinoacetate methyltransferase deficiency, etc.